Harold Pinter - Saunders, Graham, 1965- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
""Harold Pinter provides an up-to-date analysis and reappraisal concerning the work of one of the most studied and performed dramatists in the world. Drawing extensively from The Harold Pinter archive at the British Library as well as reviews and other critical materials, this book offers new insights into previously established views about his work. The book also analyses and reappraises specific key historical and contemporary productions - including a selection of Pinter's most significant screenplays. In particular, this volume seeks to assess Pinter's critical reputation and legacy since his death in 2008. These include his position as a political writer and political activist - from disassociation and neutrality on the subject until relatively late in his career when his drama sought to explicitly address questions of political dissent and torture by totalitarian regimes. The book revisits some familiar territory such as Pinter's place as a British absurdist and the role memory plays in his work, but it also sets out to explore new territory such as Pinter's changing attitudes towards gender in the light of #MeToo and queer politics and how in particular a play such as The Caretaker (1960) through several key productions have brought the issues of race into sharper focus. Part of the Routledge Modern and Contemporary Dramatist series, Harold Pinter provides an essential and accessible guide to the dramatists' work"--
Life & career : from Hackney to Holland Park -- Pinter's critical reputation, legacy, and afterlife -- Intruders & rooms -- Gender trouble -- Memory & politics -- The birthday party -- The caretaker -- The homecoming.
Keywords: Pinter, Harold, -- 1930-2008 -- Criticism and interpretation; Pinter, Harold, -- 1930-2008 -- Stage history; PERFORMING ARTS / Theater / Playwriting; PERFORMING ARTS / Theater / History & Criticism; PERFORMING ARTS / General